Analysis of the Contribution and Factors Affecting the Income of Local Chicken Farmers' Wives on Family Income in Aceh Tamiang Regency - Kiagus Muhammad Zain Basriwijaya; Dian Permata Sari Br Surbakti; Ruth Dameria Haloho; Widya Satya Nugraha; Tulus Fernando Silitonga (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
This study analyzes the income contribution of free-range chicken farmers' wives to family income and the factors influencing their income increase in Jamur Hamlet, Jelatang Village, Rantau District, Aceh Tamiang Regency. The study used a quantitative approach with a survey method. The respondents were 240 free-range chicken farmers who were selected purposively. Primary data were collected through field observations, structured interviews, and questionnaires. The wives' income contribution was measured by the proportion of their income to the family's total monthly income. To identify factors influencing family income, multiple linear regression analysis was used, with the independent variables being the wife's age and education level, working hours, and income. The analysis showed that the wife's age and education level had a positive and significant effect on family income increase. Conversely, the wife's working hours and income did not have a statistically significant effect on family income. These findings suggest that improving the quality of human resources, particularly through education and work experience, as reflected in their productive age, plays a more important role in boosting the income of free-range chicken farmers' families than simply increasing working hours. This study confirms that the wife's economic role in free-range chicken farming households is complementary and contributes to maintaining family economic stability.